Maternity care hospital trends in providing postdischarge breastfeeding supports to new mothers—United States, 2007‐2015. Issue 2 (6th November 2018) - Beauregard, Jennifer L.; Nelson, Jennifer M.; Hamner, Heather C.
Abstract: Background: Hospitals that provide maternity care can play an important role in providing or directing mothers to postdischarge breastfeeding support, which improves breastfeeding duration especially when providing multiple support modes. This study described 2007‐2015 national trends in postdischarge breastfeeding supports among United States maternity care hospitals. Methods: Data were from the Maternity Practices in Infant Nutrition and Care survey, a biennial census of maternity care hospitals in the United States and territories. Hospitals reported whether they provided nine support types, which we categorized into three support modes: physical contact (eg, return visits), active reaching out (eg, telephone calls), and referrals (eg, to lactation consultants). We calculated prevalence of each support type, each support mode, and providing all three support modes for each survey year and examined trends over 2007‐2015. For 2015, we assessed differences by hospital‐ and area‐level characteristics. Results: Prevalence of providing all three support modes increased from 24% (2007) to 31% (2015). Nearly all (99%) hospitals provided referrals in each survey year. Fewer offered physical contact and active reaching out. However, from 2007 to 2015, the prevalence of physical contact increased from 39% to 46%; active reaching out increased from 54% to 64%. In 2015, smaller and rural hospitals were more likely to provide all three discharge supports. Conclusions: Prevalence of offering referrals was high, but there is room for improvement in providing physical contact and active reaching out to ensure multiple modes of support are available to help mothers reach their breastfeeding goals.